NONSELFADJOINT DEGENERATE DIFFERENTIAL EQUATIONS OF HIGHER ORDER - Tepoyan, L.P. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2014)
In this article we consider Dirichlet problem for some class of degenerate nonselfadjoint differential equations of higher order. We prove the existence and uniqueness of the generalized solution, establish analogue of the Keldysh theorem and explore the spectral properties of the corresponding operator.